PENGARUH VIRAL MARKETING MELALUI MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN DI PANTAI TABLOLONG, KUPANG BARAT - Ruth Rosita Mboeik, Juita L. D Bessie, Abas Kasim (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2019)
This research was conducted at Tablolong Beach, West Kupang District. The purpose ofthis study is to determine the influence of Viral marketing's factors through social mediaInstagram partially and simultaneously towards the decision of visiting tourists. This study usesIntensity, Valence of opinion, and Content as independent variables, and Tourist VisitingDecisions as the dependent variable. Population in this research is Instagram users whobecome follower of @Jelajahkupang’s account and have visited Tablolong Beach more thantwice. Samples taken as many as 75 respondents by using snowball sampling technique. Thetool analysing in this research is using multiple regression analysis. The result of research hadobtained Regression Equation: Y = 3912 + 0,247X1 + 0,244X2 + 0,822X3. The result ofHypothesis Testing using t Test is obtained that the three independent variables have partiallysignificant effect on tourists’ visiting decision variables. Where the most influential variable isthe content variable with regression coefficient of 0.822, followed by the variable intensity withregression coefficient of 0.247, and variable valence of opinion with a regression coefficient of0.244. While the result of F test shows that the three independent variables simultaneously havea significant effect on tourists' visiting decision.The value of R Square 0.579 indicates that 57.9% of Tourist’s Visiting Decision variablesare influenced by independent variables in the regression equation. While the rest 42.1% ofTourist’sVisiting Decision influenced by other variables that are not discussed this research.Next researchers can do further research about viral marketing not only on social mediaInstagram but also on other social media like Facebook, Twitter, and others.